Acetaminophen Hepatotoxicity - Ramachandran, Anup; Jaeschke, Hartmut (Seminars in Liver Disease, 2019)
Acetaminophen (APAP) is one of the most popular and safe pain medications worldwide. However, due to its wide availability, it is frequently implicated in intentional or unintentional overdoses where it can cause severe liver injury and even acute liver failure (ALF). In fact, APAP toxicity is responsible for 46% of all ALF cases in the United States. Early mechanistic studies in mice demonstrated the formation of a reactive metabolite, which is responsible for hepatic glutathione depletion and initiation of the toxicity. This insight led to the rapid introduction of N-acetylcysteine as a clinical antidote. However, more recently, substantial progress was made in further elucidating the detailed mechanisms of APAP-induced cell death. Mitochondrial protein adducts trigger a mitochondrial oxidant stress, which requires amplification through a MAPK cascade that ultimately results in activation of c-jun N-terminal kinase (JNK) in the cytosol and translocation of phospho-JNK to the mitochondria. The enhanced oxidant stress is responsible for the membrane permeability transition pore opening and the membrane potential breakdown. The ensuing matrix swelling causes the release of intermembrane proteins such as endonuclease G, which translocate to the nucleus and induce DNA fragmentation. These pathophysiological signaling mechanisms can be additionally modulated by removing damaged mitochondria by autophagy and replacing them by mitochondrial biogenesis. Importantly, most of the mechanisms have been confirmed in human hepatocytes and indirectly through biomarkers in plasma of APAP overdose patients. The extensive necrosis caused by APAP overdose leads to a sterile inflammatory response. Although recruitment of inflammatory cells is necessary for removal of cell debris in preparation for regeneration, these cells have the potential to aggravate the injury. This review touches on the newest insight into the intracellular mechanisms of APAP-induced cells death and the resulting inflammatory response. Furthermore, it discusses the translation of these findings to humans and the emergence of new therapeutic interventions.
Keywords: drug-induced liver injury; apoptosis; necroptosis; mitochondrial dysfunction; DNA fragmentation; sterile inflammation